Is Blindness Close to Death? - Elif Demirkılınç Biler; Suzan Güven Yılmaz; Halil Ateş (Türk Oftalmoloji Dergisi, 2014)
The association between visual impairment and mortality has been reported in many studies. As well as some ocular diseases may be associated with increased mortality directly, visual impairment is also reportedly associated with many factors linked to higher risk of dying via indirect pathways. These include unintentional injury and increased risk of falls, reduced walking speed, lower body mass index, self-reported difficulty in physical activity and nutrition, cardiovascular diseases and even cancer, dementia, anxiety, depression, and reduced social interaction. Visual impairment also severely affect a person’s self-ranking of his or her health. Correction for these confounders has been found to attenuate the association between visual impairment and mortality, but the real mechanisms behind the association between visual impairment and mortality is still unclear. The impact of visual impairment on mortality with the decreased quality of life is an important health problem, and the ophthalmologists should be aware of it. In this review, we summarize all studies related to this subject in different patient populations. (Turk J Ophthalmol 2014; 44: 471-5)